Digital photography pocket guide - Story, Derrick (O'Reilly digital studio., 2005)
Even film diehards have a tough time resisting the instant gratification of the digital camera. Today's digital cameras are more affordable then ever before, and they deliver high quality images that are a snap to share. Plus, you can take risks with a digital camera you never would with a film camera. You waste nothing; there's no film required, and because you only print the pictures you need, digital photography is cost effective and environmentally friendly. But to take full advantage of a digital camera, you need to be an experienced photographer and an expert at digital photography too. With more than 15 years of experience as a photojournalist, author Derrick Story brings you Digital Photography Pocket Guide, 3rd Edition. For everyone who owns or will own a digital camera (and that pretty much means everyone!), this is the perfect on-the-go guide for taking top-notch digital photographs In this third edition of the bestselling pocket guide, Story expands on the basic photography techniques that he introduced in earlier editions, including an explanation of each camera component and what it does, tips for choosing just the right settings for your needs, and much more. This indispensable guide covers everything from how to shoot sports action, close ups, and night shots, to dealing with image resolution, archiving, and memory cards. Affordable and portable, Digital Photography Pocket Guide, 3rd Edition offers full-color photographs, screen shots, and line art illustrating all the topics in the guide's three main sections ("Digital Camera Components," "Standard Camera Functions," and "How Do I?"). Contents are labeled A to Z for quick reference. There's also a comprehensive table of contents and index so you'll waste no time flipping to the specific information you need--whether you want to transfer images, make a QuickTime movie, or just figure out what purpose that mystery setting on your camera serves. There's even a section of easy-to-read reference tables for quick look-up of white balance settings, exposure compensation, camera mode explanations, and plenty more.